Collaborative Interpersonal Psychotherapy for HIV‐Positive Women in Kenya: A Case Study From the Mental Health, HIV and Domestic Violence (MIND) Study. Issue 8 (27th July 2016) - Opiyo, Elizabeth; Ongeri, Linnet; Rota, Grace; Verdeli, Helen; Neylan, Thomas; Meffert, Susan
Abstract : We examine the efficacy of nonspecialists delivering interpersonal psychotherapy (IPT) to HIV‐positive (HIV+) women. We describe a case in which local personnel without prior mental health training delivered IPT for the treatment of depression and posttraumatic stress disorder in an HIV+ woman who reported experiencing gender‐based violence and was enrolled in HIV care at the Family AIDS, Care, Education and Services program in Kisumu, Kenya.